The Rise and Fall of Cork Model Collections in Britain. (17th November 2017) - Gillespie, Richard
Abstract: Commencing in the late 1760s, cork models of classical monuments in Italy were purchased by wealthy British collectors while on their Grand Tour. Initially commissioned by tourists with specific antiquarian and architectural interests, the models were an expression of the collector's knowledge of classical history and of their Neoclassical sensibility. Models soon appeared in the Society of Antiquaries of London and the British Museum, in the private displays of Charles Townley and John Stuart, Earl of Bute, and in George III's royal collection. In the early 1800s, architect John Soane began purchasing models from the secondary market for his house museum. Interest in cork architectural models waned during the Nineteenth Century. Descendants of the original owners transferred them to public institutions, while museums that had at first enthusiastically welcomed the donations or made their own purchases, relegated the models to storage. In the twentieth century the majority of the models were discarded or lost. This paper explores the reasons for the enthusiastic acquisition of architectural cork models and their subsequent demise.